El pentágono pedagógico de los parques: dispositivo conceptual para el análisis educativo de los espacios verdes urbanos como sitios emergentes de aprendizaje (Ensayos) - Valladares Riveroll, Liliana (2023)
This article proposes a conceptual device for the techno-pedagogical analysis of urban green spaces. It explores how urban parks are integrated into the networks of educational and learning practices that occur in the public space and if it is possible to organize them as pedagogical strategies. The Pedagogical Pentagon of Parks (PPP) is proposed as a conceptual, analytical lens to ensure that urban parks and everything happening and present in them communicate educationally. The PPP is a framework of five articulated categories (public pedagogy, learning cities, smart learning, cyberparks, and museographic language) that transform our view towards the parks to intervene in them as emerging learning territories.